The Changing Trends in Education - Gül, Leman Figen (Frontiers in ICT, 2015)
With the recent developments in information and communication technologies (ICTs), there is a significant change in our daily life. Eventually, integrating ICTs into teaching and learning offers significant potentials for higher education institutions and new challenges for educators, through their capacity to facilitate new kind of education in the digital environments. As a result, there have been significant changes in several professions’ curricula such as design, business, medicine, engineering, etc. to accommodate new demands, opportunities, processes and potentials provided by digital media and computational tools.